How do income and the debt position of households propagate public into private spending? - Rüth, Sebastian; Simon, Camilla (Discussion paper series, 2020)
We study the household sector's post-tax income and debt position as propagation mechanisms of public into private spending, in postwar U.S. data. In structural VARs, we obtain the consumption "crowding-in puzzle" for surges in public spending and show this consumption response to be accompanied by a persistent increase in disposable income. Endogenously reacting income, however, is insufficient to rationalize conditional comovement of private and public spending: once we hypothetically force (dis)aggregate measures of income to their pre-shock paths, consumption still rises. Corroborating these findings within an external-instruments-identified VAR, which constitutes an adequate laboratory for the simultaneous interplay of financial and macroeconomic time-series, we provide causal evidence of fiscal stimulus prompting households to take on more credit. This favorable debt cycle is paralleled by dropping interest rates, narrowing credit spreads, and in ating collateral prices, e.g., real estate prices, suggesting that softening borrowing constraints support the accumulation of debt and help rationalizing the absence of crowding-out.